THE CRIMINAL SANCTIONS AGAINST TRANSNATIONAL SMUGGLING FIREARMS THROUGH SEA ROUTES IN INDONESIAN TERRITORY: Based on United Nations Convention against Transnational Organized Crime - Islamia, Nabila; Prasetyo , Dossy Iskandar (Acitya Wisesa: Journal of Multidisciplinary Research, 2022)
The existence of TOC (Transnational Organized Crime) is considered to be a new threat to security, one example of TOC is the smuggling of firearms between countries through sea routes. This crime is a security threat to individuals, nationally and internationally. In international regulations, smuggling firearms between countries by organized groups is regulated in the United Nations Convention against Transnational Organized Crime which was supervised by General Assembly resolution 55/25 in 15 November 2000. In addition, there are also several national instruments, such as Law Emergency No. 12/1951, Terrorism Law and Customs Law. Indonesia has become a potential place for smuggling firearms illegally because of many internal conflicts and terrorism cases that have occurred. Most of the perpetrators of this crime use the sea route for trade it. Therefore, the government implements law enforcement and sanctions. The researcher used a normative-juridical research method, research based on a statutory approach, review of all laws and related regulations of its topic. This research used Law No. 5/2009 concerning Ratification of the United Nations Conventions against Transnational Organized and other relevant laws as primary data. The secondary data of this research is the researcher's legal argument in the perspective of a concrete case in the field, an approach to cases that are related to firearms smuggling and illegal arms trade. The objectives of this research are to find out smuggling firearms management efforts, and to analyze the criminal sanctions against this case.